Comparative Analysis of Low Versus High Implant Density in Decreasing Cobb Angle in Lenke Type 1 Adolescents Idiopathic Scoliosis (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To compare low versus high implant density in decreasing Cobb angle in Lenke Type 1 Adolescent Idiopathic Scoliosis(AIS) treated with segmental spinal instrumentation and pedicle screws.Methods: This retrospective Cohort study was conducted at Department of Orthopedic and Spine Surgery, Ghurki Trust Teaching Hospital/ Lahore Medical and Dental College, Lahore. The medical records of patients between 15th June 2015 to 15th June 2019 who underwent segmental spinal instrumentation for Lenke type 1 adolescent idiopathic scoliosis were reviewed. Low implant density was defined as patients with pedicle screw density per fused segment of 60 %( ?1.2) or less while high density patients had more than 60 % (> 1.2) screw density. Radiographs were evaluated preoperatively for Cobb angle of main thoracic curve, sagittal and lumbar modifier. Postoperative evaluation included postoperative Cobb angle, percent Cobb angle decease, implant density and implant cost. Independent sample t-test, paired Sample t-test and Chi-square test of association were applied to compare preoperative and postoperative variables between two groups. P